Development of Blog-Based Mathematics Learning Media - Muna, Faizul; Fuadi, Muhammad Hilman; Nurhuda, Abid (Yayasan Pendidikan dan Kemanusiaan Hurriah Aceh, 2023)
The rapid development of technology goes hand in hand with its use in learning media. One of them is in the form of a blog, especially in learning that is often considered difficult and boring, such as mathematics. So this study aims to describe the development of Blog media in learning mathematics as well as validity. The method used is Research and Development (R&D) with the ADDIE development model (Analyze, Design, Development, Implementation, Evaluation) aimed at research subjects of 26 students in class 8C at MTsN Kota Batu. The results showed that the Development of Blog-Based Mathematics Learning Media had a media validity score of 95.39% and a material validation result of 87.5%, both of which were categorized as very good. Meanwhile, the media readability questionnaire in this study has a value of 85.19% in the very good category.